Adaptive diversity of beech seedlings under climate change scenarios - Varsamis, Georgios; Papageorgiou, Aristotelis C; Merou, Theodora; Takos, Ioannis; Malesios, Chrisovalantis; Manolis, Apostolos; Tsiripidis, Ioannis; Gailing, Oliver (PeerJ Preprints, 2018)
The ability of beech (Fagus sylvatica L.) populations to adapt to the ongoing climate change is crucial for the maintenance of economic and social benefits and for the conservation of biodiversity in Europe and especially in the southeastern part of the continent, where environmental change is expected to be more intense. Beech populations in the region cover multiple ecological conditions at a small geographical range and have a complex biogeographical background involving several postglacial lineages originating from distant or local refugia. In this study, we tested the existing adaptive potential of eight beech populations from two provenances in N.E. Greece (Evros and Drama), under simulated controlled climate change conditions in a growth chamber and in the field. In the growth chamber, simulated conditions of temperature and precipitation for the year 2050 were applied for three years, under two different irrigation schemes, a non-frequent (A1) and a frequent one (A2). Seedling survival, growth and leaf phenological traits were used as adaptive traits. The results showed that beech seedlings were generally able to survive under climate change conditions and showed adaptive differences among provenances and populations. Furthermore, beech genotypes demonstrated an impressive phenotypic plasticity by changing the duration of their growing season allowing them to avoid environmental stress and high selection pressure. Different populations and provenances were connected with different adaptation strategies, that relate mainly to the temporal distribution patterns of precipitation and temperature, rather than the average annual or monthly values of these measures. Additionally, different adaptive strategies appeared among beech seedlings when the same amount of water was distributed differently within each month. This indicates that the physiological response mechanisms of beech individuals are very complex and depend on several interacting parameters. For this reason, the choice of beech provenances for translocation and use in afforestation or reforestation projects should consider the small scale ecotypic diversity of the species and view multiple environmental and climatic parameters in connection to each other.
Keywords: Fagus; phenology; survival; height; adaptation; common garden experiment; plasticity; climate change; provenance test